Considerations for Using a Geographic Information System to Assess Environmental Supports for Physical Activity - Dwayne E. Porter; Karen A. Kirtland; Matthew J. Neet; Joel E. Williams; Barbara E. Ainsworth (Centers for Disease Control and Prevention, 2004)
The use of a geographic information system (GIS) to study environmental supports for physical activity raises several issues, including acquisition and development, quality, and analysis. We recommend to public health professionals interested in using GIS that they investigate available data, plan for data development where none exists, ensure the availability of trained personnel and sufficient time, and consider issues such as data quality, analyses, and confidentiality. This article shares information about data-related issues that we encountered when using GIS to validate responses to a questionnaire about environmental supports for physical activity.